2015
DOI: 10.1080/14786419.2015.1043632
|View full text |Cite
|
Sign up to set email alerts
|

Lavandin (Lavandula × intermedia Emeric ex Loiseleur) essential oil from Spain: determination of aromatic profile by gas chromatography–mass spectrometry, antioxidant and lipoxygenase inhibitory bioactivities

Abstract: Lavandin (Lavandula × intermedia Emeric ex Loiseleur) essential oils (EOs), from Abrial, Super and Grosso cultivars, cultivated and extracted in the South East of Spain, were analysed by using GC/MS to determine their composition, in both relative (peak area) and absolute (using standard curves) concentrations. Linalool (34-47%), linalyl acetate (17-34%), camphor (4-9%) and eucalyptol (3-7%) were determined as the main molecules. This characterisation was completed with the enantioselective gas chromatography,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 30 publications
(38 reference statements)
5
23
0
1
Order By: Relevance
“…Other authors have observed in the steam‐distilled oil L . × intermedia Super contents of linalool (39 – 46%) and linalyl acetate (20 – 34%) comparable to our data . However, the contents of linalool and linalyl acetate depend on the hydrodistillation time and reach maximum yields of 53.5% and 41.5%, respectively, when the duration of the distillation is 30 – 35 min .…”
Section: Resultssupporting
confidence: 89%
“…Other authors have observed in the steam‐distilled oil L . × intermedia Super contents of linalool (39 – 46%) and linalyl acetate (20 – 34%) comparable to our data . However, the contents of linalool and linalyl acetate depend on the hydrodistillation time and reach maximum yields of 53.5% and 41.5%, respectively, when the duration of the distillation is 30 – 35 min .…”
Section: Resultssupporting
confidence: 89%
“…The most abundant compounds were oxygenated monoterpenes (91.2 %) such as linalool (23.1 %), camphor (16.3 %), 1,8-cineole (14.5 %), linalool acetate (10.0 %), borneol (5.2 %) and caryophyllene oxide (2.1 %). Similar oil patterns have been reported in previously published papers (Bajalan et al, 2017;Blažeković et al, 2018;Carrasco et al, 2016;Garzoli et al, 2020). Sesquiterpenes and their oxygenated forms are much less abundant in the essential oil than oxygenated monoterpenes with total values of 0.7 % and 3.3 %, respectively.…”
Section: Essential Oil Chemical Compositionsupporting
confidence: 88%
“…Although α ‐thujone is not the best chelating compound, its high concentration in the SoEOs may explain why SoEO‐4 and ‐2 showed the greatest activity. Complexation of ferrous cations could be due to the oxygen atoms of the ether, ketone, and alcohol groups, which contain non‐binding electron pairs …”
Section: Resultsmentioning
confidence: 99%
“…Complexation of ferrous cations could be due to the oxygen atoms of the ether, ketone, and alcohol groups, which contain non-binding electron pairs. [59] Inhibitory Activity Although a-thujone is not the best inhibitor of this enzyme, the comparatively high amount found in SoEO-2 and -4, along with the concentration of limonene, may be responsible for the differences between the SoEOs. Nordihydroguaiaretic acid (NDGA) had an IC 50 = 339.4 AE 9.4 lM, which agrees with the values found in the relevant literature.…”
Section: Antioxidant Activitymentioning
confidence: 99%